ELABORAÇÃO DE UMA CARTILHA DIGITAL SOBRE INOVAÇÕES TECNOLÓGICAS EM CONTABILIDADE PARA DISCENTES E PROFISSIONAIS DAS CIÊNCIAS CONTÁBEIS - JUNIOR, ADEMIR CIRICO (2019)
The objective of this study was to elaborate a digital booklet about technological innovations in accounting for students and professionals of the Accounting Sciences of Paraná State. Therefore, it was necessary, a priori, to use bibliographic research, from secondary sources, with consultation of books, scientific articles, monographs, dissertations and theses, as a theoretical basis for the achievement of the objectives outlined in this study. In addition, in parallel, as a support element, a bibliometric and patentometric research was conducted regarding the survey of studies already carried out on technological innovations in the accounting area, as well as the identification of technologies deposited in the base of the National Institute of Industrial Property ( INPI) applicable to accounting, in order to identify existing demands at both institutional and corporate levels. Considering the changes that have taken place in accounting firms with innovations in the business model, in online accounting firms, in view of the rise in customer demand for accounting firms offering more agile, safe and practical services, It is necessary that both students and accounting professionals seek constant updates and professional improvement to be inserted in the market, adapting to technological advances in the area in which they operate. Thus, in light of the above, it is emphasized that this study proposes the sharing of information related to technological innovations in the accounting area, free of charge and digitally, for students and professionals of the Accounting Sciences, with contributory reflexes for sustainable development, that is, development. environment, by making the booklet available in digital media, contributing to the reduction of print volumes and certainly avoiding the accumulation of papers, as well as the development of the economy and society, through the sharing of the didactic and instructional booklet, no acquisition costs. Therefore, the results of this study contribute to the economic and intellectual development of students and accounting professionals, as well as the development of the environment, with a central focus on contributions to the community.